The Green Value of Your Woods: A Summary of Ecosystem Services Provided by Forest Stewardship Lands in Florida - Rose Godfrey; Chris Demers; Francisco Escobedo; Damian Adams; Michael Andreu (EDIS)
Lands enrolled in voluntary forest management and conservation programs, like the Forest Stewardship Program, promote good land management practices. In addition to benefiting the landowners enrolled in these programs, good land management provides ecosystem services to society. The Stewardship Ecosystem Services Survey calculated the physical and economic benefits of water resource protection, carbon sequestration and storage, timber production, and wildlife conservation. This 2-page fact sheet was written by Rose Godfrey, Chris Demers, Francisco Escobedo, Damian Adams, and Michael Andreu, and published by the UF Department of School of Forest Resources and Conservation, September 2013.